Twentieth century authors : A biographical dictionary of modern literature (New York H.W. Wilson Company, 1942)
This work aims to provide a foundation volume of authoentic biographical information on the writers of this centure, of all nations, whose books are familiar to readers of English.
Summary taken from preface in beginning of the book.
18094
Keywords: Authors -- Biographies -- Reference material -- Twentieth Century through 1941 -- World wide